Antimicrobial-associated adverse events in neonates: an integrated literature review and FAERS pharmacovigilance analysis - Yan Zhang; Jiajia Wang; Baomei Liu; Mingfang Wang; Li Zhuang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Identification of the SlRCC1 gene family and characterization of SlRCC1-13 in cold stress response in tomato (Solanum lycopersicum) - Huixin Zhang; Xueyao Zeng; Yixiao Bai; Yuxin Liu; Rui LV; Fulei Mo; Mingfang Feng; Shusen Liu; Xiuling Chen; Aoxue Wang (Plant Science, 2026)

IMEA-Net: An edge-sensitive network for cropland change detection in high-resolution remote sensing images - Xiaoli Yuan; Li Chen; Jiang Zhang; Guoxiong Zhou; Mingfang Wang; Liujun Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Improving the catalytic performance of glutamate decarboxylase based on sequence co-evolution analysis - Haifeng Pan; Siyi Wang; Yinyi Zhang; Yong Liu; Mingfang Wu; Peilian Wei; Changjiang Lyu; Wenna Bao (Food Bioscience, 2026)

RTCrownNet: A dual-channel deep learning framework for accurate rubber tree crown extraction from UAV LiDAR point clouds - Li Li; Xiangjun Wang; Guoxiong Zhou; Huaiqing Zhang; Yongfei Xue; Mingfang He; Genhua Liu; Hengrui Wang; Hao Li (Computers and Electronics in Agriculture, 2025)

BFlow and Eckhardt methods perform best among non-tracer-based baseflow separation methods - Qiaoqiao Wang; Qiang Li; Yanli Qin; Xuanjiao Chai; Hongli Chen; Yaping Wang; Mingfang Zhang; Dengfeng Liu (Journal of Hydrology, 2025)

Effectiveness of Salicornia europaea-Derived Biochar in Immobilizing Cadmium in Acidic Soil - Shaoqing Ge; Lei Wang; Mingfang Hu; Zhenyong Zhao; Changyan Tian (Journal of Soil Science and Plant Nutrition, 2025)

AMF: A multi-modal framework for crop leaf diseases segmentation - Yang Hu; Gang Wang; Exian Liu; Jiale Zhu; Mingfang He (Computers and Electronics in Agriculture, 2025)

The Role of Iron and Ferroptosis in the Pathogenesis of L-Arginine-Induced Acute Pancreatitis - Peng Zhang; Lulu Fan; Mingfang Teng; Qianhui Wu; Wang Jiaqing; I. P. Korotkova (Bulletin of Experimental Biology and Medicine, 2025)

Tree growth response to the 2022 compound drought and heatwave on the eastern Qinghai-Tibetan Plateau - Zhenzhen Wang; Meiying Ji; Jianqiong Luo; Mingfang Zhang; Ning Miao (Forest Ecology and Management, 2025)

The 3PM transformation potential of minimal residual disease in solid tumor management: a bibliometric analysis and review - Yining Chen; Xin Li; Suya Zhao; Yuchong Zhang; Haixu Wang; Fangjian Na; Qi Guan; Zhi Li; Heming Li; Mingfang Zhao (EPMA Journal, 2025)

Efficient photoelectrocatalytic simultaneous removal of antibiotic and Cr(VI) upon novel ternary plasma Ag/AgVO3@3D TiO2: Insight into the synergistic mechanism of redox - Yuqing Gao; Yuzhou Jin; Yu Hu; Mingfang Li; Xuejiang Wang; Haiying Ma; Ya-nan Zhang (Chemosphere, 2025)

ESR1-dependent suppression of LCN2 transcription reverses autophagy-linked ferroptosis and enhances sorafenib sensitivity in hepatocellular carcinoma - Mingfang Xu; Tran Sy Trung; Zhiyong Zhu; Shijia Li; Shicheng Gong; Nuo Cheng; Peng Zhou; Shuai Wang (Journal of Physiology and Biochemistry, 2025)

Ratio fluorescence and smartphone-assisted colorimetry dual-mode detection of creatinine based on F, B, N-doped of red fluorescent carbon dots - Qiqing Chen; Wenhao Liu; Zengcheng Du; Yulan Li; Chaoying Zeng; Mingfang Zhu; Mengjiao Pang; Yanjie Wang (Analytica Chimica Acta, 2025)

WCG-VMamba: A multi-modal classification model for corn disease - Haoyang Wang; Mingfang He; Minge Zhu; Genhua Liu (Computers and Electronics in Agriculture, 2025)

Rainfall intensities determine accuracy of canopy interception simulation using the Revised Gash model - Mengliang Ma; Qiang Li; Yaping Wang; Jin Liang; Jiangyao Wang; Jinliang Liu; Mingfang Zhang (Agricultural and Forest Meteorology, 2025)

Local considerations are the key to managing global forests for water - Xiaohua Wei; Julia Jones; Yiping Hou; Shirong Liu; Heidi Asbjornsen; Zhiqiang Zhang; Nadeem Shah; Yanhui Wang; Mingfang Zhang; Irena Creed; Ge Sun; Antonio del Campo; et al. (Science Bulletin, 2025)

Microbes: Drivers of Chenpi manufacturing, biotransformation, and physiological effects - Yanjiao Fu; Chao Wang; Zhipeng Gao; Yanfang Liao; Mingfang Peng; Fuhua Fu; Gaoyang Li; Donglin Su; Jiajing Guo; Yang Shan (Food Chemistry, 2025)

Hydrogel antifouling platform with highly specific H+-responsiveness: Application in carbon capture and conversion - Jie Yin; Yuanfang Li; Yijie Huang; Yuhan Wang; Mingfang Yang; Ruo Yuan; Ying Zhuo; Zhe-Han Yang (Chemical Engineering Journal, 2025)

LVF: A language and vision fusion framework for tomato diseases segmentation - Yang Hu; Jiale Zhu; Guoxiong Zhou; Mingfang He; Mingjie Lv; Junhui Wang; Aibin Chen; Jinsheng Deng; Yichu Jiang (Computers and Electronics in Agriculture, 2024)

Impacts of artificial intelligence on carbon emissions in China: in terms of artificial intelligence type and regional differences - Mingfang Dong; Guo Wang; Xianfeng Han (Sustainable Cities and Society, 2024)

Citrus aurantium L. 'Daidai' physiological premature fruit drop relieves obesity in high-fat-diet-fed mice via modulating lipid metabolism and gut microbiota - Mingfang Peng; Chao Wang; Zhipeng Gao; Fuhua Fu; Gaoyang Li; Donglin Su; Lvhong Huang; Jiajing Guo; Yang Shan (Food Bioscience, 2024)

Effects of halophyte Suaeda salsa continuous cropping on physical and chemical properties of saline soil under drip irrigation in arid regions - Sihai Liu; Ning Wang; Dongze Li; Changyan Tian; Ke Zhang; Mingfang Hu; Haishan Niu; Zhenyong Zhao (Agriculture, Ecosystems & Environment, 2024)

The first detection of mpox virus DNA from wastewater in China - Jin Xu; Chao Liu; Qun Zhang; Haining Zhu; Feng Cui; Zhiqiang Zhao; Mingfang Song; Bo Zhou; Yunxiao Zhang; Peilong Hu; Lei Li; Qin Wang; et al. (Science of The Total Environment, 2024)

Fractional nutrient uptake model of plant roots - Yue Wang; Mingfang Lin; Quanbiao Gong; Zhonghui Ou (BioSystems, 2024)

A large presence/absence variation in the promotor of the ClLOG gene determines trichome elongation in watermelon - Yuyuan Ma; Yu Wang; Zhiqin Zhou; Runqin Zhang; Yiru Xie; Yihan Zhang; Yongming Bo; Xiaolong Lyu; Jinghua Yang; Mingfang Zhang; Zhongyuan Hu (Theoretical and Applied Genetics, 2024)

Serum Copper/Zinc Ratio in Overweight and Obese Children: a Cross-Sectional Study - Mu Du; Mingfang Qiu; Ye Qian; Tianqi Wang; Xiaobo Chen (Biological Trace Element Research, 2024)

Quercetin-targeted AKT1 regulates the Raf/MEK/ERK signaling pathway to protect against doxorubicin-induced nephropathy in mice - Wang Yufang; Liu Mingfang; Huang Nan; Wang Tingting (Tissue and Cell, 2023)

Steric heights of submesoscale processes and internal gravity waves in the subtropical northwestern Pacific and northern South China Sea as revealed by moored observations - Mingfang Miao; Zhiwei Zhang; Jinchao Zhang; Yue Wang; Wei Zhao; Jiwei Tian (Progress in Oceanography, 2023)

Artificial intelligence, industrial structure optimization, and CO2 emissions - Mingfang Dong; Guo Wang; Xianfeng Han (Environmental Science and Pollution Research, 2023)

Natural polymer Nicandra physaloides (L.) Gaertn seed gum mediated assembly of hydroxyapatite assembly as versatile sponge for water pollution control - Xudong Wu; Yazhou Wang; Li Zhou; Chengkun Cai; Mingfang Hu; Xiaofang Yu; Rong He; Wenkun Zhu (Journal of Cleaner Production, 2023)

Molecularly imprinted polymers embedded with double perovskite quantum dots: A ratiometric fluorescence sensor for visible and fluorescent determination of Rhein - Rongkun Zhu; Zengcheng Du; Mingfang Zhu; Huanru Liang; Shumei Wang; Qing Zhou; Rui Li; Yulan Li; Chaoying Zeng; Wenhao Liu; Qiqing Chen (Chemical Engineering Journal, 2023)

Anti-obesity mechanism of Ganpu tea revealed by microbiome, metabolome and transcriptome analyses - Yanfang Liao; Chen Wang; Zhipeng Gao; Zhaoping Pan; Mingfang Peng; Jie Ma; Yujiao Qian; Jiajing Guo; Fuhua Fu (Food Chemistry, 2023)

Effect of temperature on the life table parameters and high-temperature lethality of Tyrophagus putrescentiae - Peipei Zhu; Shan Yang; Yuanfa Yang; Hui Ai; Mingfang Chen; Xi Wang; Ling Zhong; Bin Xia; Zhiwen Zou (Journal of Stored Products Research, 2023)

Differences in the effectiveness of the high-efficient concentrated pretreatment method on the norovirus detection in oysters and mussels - Yijing Li; Liang Xue; Junshan Gao; Weicheng Cai; Yanhui Liang; Zilei Zhang; Linping Wang; Xiaojing Hong; Luobing Meng; Mingfang Xu; Qingping Wu; Jumei Zhang (International Journal of Food Microbiology, 2023)

Correction to: Dietary supplementation with synbiotics improves growth performance, antioxidant status, immune function, and intestinal barrier function in broilers subjected to cyclic heat stress - Mingfang Du; Yefei Cheng; Yueping Chen; Shiqi Wang; Haoran Zhao; Chao Wen; Yanmin Zhou (Environmental Science and Pollution Research, 2022)

Dietary supplementation with synbiotics improves growth performance, antioxidant status, immune function, and intestinal barrier function in broilers subjected to cyclic heat stress - Mingfang Du; Yefei Cheng; Yueping Chen; Shiqi Wang; Haoran Zhao; Chao Wen; Yanmin Zhou (Environmental Science and Pollution Research, 2022)

Application of galactinol to tomato enhances tolerance to cold and heat stresses - Yudong Liu; Li Zhang; Jian Ma; Sida Meng; Chunpeng Pang; Xiaomeng Zhao; Huidong Zhang; Shou Wang; Tao Xu; Yi He; Yufeng Liu; Mingfang Qi (Horticulture, Environment, and Biotechnology, 2022)

Nitrogen transformation and microbial community structure varied in apple rhizosphere and rhizoplane soils under biochar amendment - Hui Cao; Mingfang Jia; Mi Xun; Xiushuang Wang; Kun Chen; Hongqiang Yang (Journal of Soils and Sediments, 2021)

Identification of salt-responsive genes using transcriptome analysis in Dunaliella viridis - Zhenyu Xing; Xiangnan Gao; Mingfang Wang; Yuting Cong; Xiaojie Chai (Journal of Applied Phycology, 2020)

Vegetation cover—another dominant factor in determining global water resources in forested regions - Xiaohua Wei; Qiang Li; Mingfang Zhang; Krysta Giles‐Hansen; Wenfei Liu; Houbao Fan; Yi Wang; Guoyi Zhou; Shilong Piao; Shirong Liu (Global Change Biology, 2018)
Forested catchments provide critically important water resources. Due to dramatic global forest change over the past decades, the importance of including forest or vegetation change in the assessment of water resources under climate change has been highly recognized by Intergovernmental Panel on Climate Change (IPCC); however, this importance has not yet been examined quantitatively across the globe. Here, we used four remote sensing‐based indices to represent changes in vegetation cover in forest‐dominated regions, and then applied them to widely used models: the Fuh model and the Choudhury‐Yang model to assess relative contributions of vegetation and climate change to annual runoff variations from 2000 to 2011 in forested landscape (forest coverage >30%) across the globe. Our simulations show that the global average variation in annual runoff due to change in vegetation cover is 30.7% ± 22.5% with the rest attributed to climate change. Large annual runoff variation in response to vegetation change is found in tropical and boreal forests due to greater forest losses. Our simulations also demonstrate both offsetting and additive effects of vegetation cover and climate in determining water resource change. We conclude that vegetation cover change must be included in any global models for assessing global water resource change under climate change in forest‐dominant areas.

The role of gibberellins and auxin on the tomato cell layers in pericarp via the expression of ARFs regulated by miRNAs in fruit set - Xin Liu; Tao Xu; Xiufen Dong; Yudong Liu; Zihan Liu; Zihang Shi; Yanling Wang; Mingfang Qi; Tianlai Li (Acta Physiologiae Plantarum, 2016)

Prediction of northern summer low-frequency circulation using a high-order vector auto-regressive model - Lei Wang; Mingfang Ting; David Chapman; Dong Eun Lee; Naomi Henderson; Xiaojun Yuan (Climate Dynamics, 2016)

Small RNA and degradome sequencing reveals microRNAs and their targets involved in tomato pedicel abscission - Tao Xu; Yanling Wang; Xin Liu; Shuangshuang Lv; Chaoyang Feng; Mingfang Qi; Tianlai Li (Planta, 2015)

Temporal and Spatial Distribution of Auxin Response Factor Genes During Tomato Flower Abscission - Xiaoxi Guan; Tao Xu; Song Gao; Mingfang Qi; Yanling Wang; Xin Liu; Tianlai Li (Journal of Plant Growth Regulation, 2014)